2013
DOI: 10.3389/fimmu.2013.00214
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Adjuvants: Mode of Action

Abstract: Vaccines were first introduced more than 200 years ago and have since played a key role in the reduction of morbidity and mortality caused by infectious diseases. Many of the safest and most effective vaccines in use today are based on attenuated live viruses, as they mimic a live infection without causing disease. However, it is not always practical to take this approach, such as when it may not be safe to do so (e.g., for viruses that cause chronic infections such as HIV) or may not be feasible to manufactur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
90
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(97 citation statements)
references
References 49 publications
0
90
0
6
Order By: Relevance
“…Differences between MF59 and alum in shaping the GC responses may reflect their different mechanisms of action to activate the innate immune system [extensively reviewed by De Gregorio et al (11)]. Whereas alum efficiently delivers the Ag to conventional DC (9,35), MF59 generates an immunocompetent environment at the injection site that favors the trafficking and activation of monocytes (14,15,36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences between MF59 and alum in shaping the GC responses may reflect their different mechanisms of action to activate the innate immune system [extensively reviewed by De Gregorio et al (11)]. Whereas alum efficiently delivers the Ag to conventional DC (9,35), MF59 generates an immunocompetent environment at the injection site that favors the trafficking and activation of monocytes (14,15,36).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, alum was shown to bind lipids on the surface of APCs and trigger cellular activation cascades leading to initiation of an immune response, but without itself being internalized by the cells (9), suggesting an indirect role in delivering Ag into the Agprocessing pathway; however, other studies have shown that alum is internalized by APCs, resulting in endosomal destabilization (10). In contrast, MF59 primary mechanism of action resides in the generation of an immunocompetent environment at the injection site (muscle), characterized by the release of local extracellular ATP, expression of activation makers on resident DC, and secretion of chemokines that strongly increase phagocytic cells trafficking toward the injection site and the draining lymph nodes (LNs) (11)(12)(13)(14)(15). Unlike alum, MF59 does not directly activate DC, but rather promotes cell migration, a more efficient Ag uptake, and more Ag-loaded APCs in draining LNs compared with alum or nonadjuvanted vaccines (12,13,15).…”
mentioning
confidence: 99%
“…Afterwards, aMSCP were washed 5x with 500 µl PFB to remove residual DVH 165 solution. Finally, aMSCP were suspended in 700 µl formulation buffer (FB) consisting of PFB 166 with 250 µg polyinosinic:polycytidylic acid (poly I:C)/ml (Invivogen, Toulouse, France) and 167 250 µg CpG/ml (Eurofins Genomics, Ebersberg, Germany) as adjuvant [29]. The aMSCP system 168 was optimized to contain a minimum antigen content of [30].…”
Section: Materials and Methods 103mentioning
confidence: 99%
“…Removal or eradication of intracellular pathogens by the cell-mediated immune response is highly desired for the next generation of vaccines (3,4). Several lines of evidence suggest that an appropriate adjuvant can strongly enhance the immunogenicity of antigens (5)(6)(7). Such adjuvants must be first recognized by the innate immune cells in order to induce adaptive immunity.…”
mentioning
confidence: 99%
“…Alum-based adjuvants (alum) that are approved for clinical use in humans can increase humoral immune responses without unacceptable side effects. However, they elicit cell-mediated immune responses only poorly (1,5). Therefore, ideal adjuvants are expected to effectively induce not only humoral but also cell-mediated immune responses.…”
mentioning
confidence: 99%